Essential role for autophagy during invariant NKT cell development - Salio, M; Puleston, D; Mathan, T; Shepherd, D; Stranks, A; Adamopoulou, E; Veerapen, N; Besra, G; Hollander, G; Simon, A; Cerundolo, V (National Academy of Sciences, 2014)
Autophagy is an evolutionarily conserved cellular homeostatic pathway essential for development, immunity, and cell death. Although autophagy modulates MHC antigen presentation, it remains unclear whether autophagy defects impact on CD1d lipid loading and presentation to invariant natural killer T (iNKT) cells and on iNKT cell differentiation in the thymus. Furthermore, it remains unclear whether iNKT and conventional T cells have similar autophagy requirements for differentiation, survival, and/or activation. We report that, in mice with a conditional deletion of the essential autophagy gene Atg7 in the T-cell compartment (CD4 Cre-Atg7(-/-)), thymic iNKT cell development--unlike conventional T-cell development--is blocked at an early stage and mature iNKT cells are absent in peripheral lymphoid organs. The defect is not due to altered loading of intracellular iNKT cell agonists; rather, it is T-cell-intrinsic, resulting in enhanced susceptibility of iNKT cells to apoptosis. We show that autophagy increases during iNKT cell thymic differentiation and that it developmentally regulates mitochondrial content through mitophagy in the thymus of mice and humans. Autophagy defects result in the intracellular accumulation of mitochondrial superoxide species and subsequent apoptotic cell death. Although autophagy-deficient conventional T cells develop normally, they show impaired peripheral survival, particularly memory CD8(+) T cells. Because iNKT cells, unlike conventional T cells, differentiate into memory cells while in the thymus, our results highlight a unique autophagy-dependent metabolic regulation of adaptive and innate T cells, which is required for transition to a quiescent state after population expansion.